2018
DOI: 10.4081/ejh.2018.2847
|View full text |Cite
|
Sign up to set email alerts
|

LOX-1 deficient mice show resistance to zymosan-induced arthritis

Abstract: Recent data suggest that the lectin-like oxidized low-density lipoprotein (ox-LDL) receptor-1 (LOX-1)/ox-LDL system may be involved in the pathogenesis of arthritis. We aimed to demonstrate the roles of the LOX- 1/ox-LDL system in arthritis development by using LOX-1 knockout (KO) mice. Arthritis was induced in the right knees of C57Bl/6 wild-type (WT) and LOX-1 KO mice via zymosan injection. Saline was injected in the left knees. Arthritis development was evaluated using inflammatory cell infiltration, synovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…60 Therefore, in vitro and in vivo studies indicate involvement of the LOX-1/ox-LDL system in OA. Recently, Xinhua et al 61 showed possible involvement of the LOX-1/ox-LDL system in pathogenesis and progression of human intervertebral disc degeneration or herniation. These results indicate that the LOX-1/ox-LDL system is strongly involved in the pathogenesis of OA (Table 1, Figure 1).…”
Section: Evidence For Involvement Of Lox-1/ox-ldl In Oamentioning
confidence: 99%
“…60 Therefore, in vitro and in vivo studies indicate involvement of the LOX-1/ox-LDL system in OA. Recently, Xinhua et al 61 showed possible involvement of the LOX-1/ox-LDL system in pathogenesis and progression of human intervertebral disc degeneration or herniation. These results indicate that the LOX-1/ox-LDL system is strongly involved in the pathogenesis of OA (Table 1, Figure 1).…”
Section: Evidence For Involvement Of Lox-1/ox-ldl In Oamentioning
confidence: 99%
“…International Publisher of LOX-1/Ox-LDL system may be involved in the pathogenesis of arthritis by using LOX-1 knockout mice, additionally, LOX-1-positive synovial cells and chondrocytes may be potential therapeutic targets for arthritis prevention [8].The current review on regulation, signaling and various effects of LOX-1 has indicated the key contribution of LOX-1 to the atherogenic process. Anti-LOX-1 therapy has been shown to decrease inflammation, oxidative stress and atherosclerosis, making LOX-1 a promising target of therapy for atherosclerosis and related disorders [9].…”
Section: Ivyspringmentioning
confidence: 99%
“…Previous studies have shown that LOX-1 knockout or LOX-1 blocking antibodies can inhibit the inflammatory response (Hashimoto et al, 2018), lipid deposition (Mehta et al, 2007), and apoptosis (Pirillo et al, 2013;Schaeffer et al, 2009) induced by Ox-LDL. As HNG restrained LOX-1 content induced by Ox-LDL, it is uncertain whether the role of reducing lipid accumulation is mediated through the inhibition of LOX-1 expression.…”
Section: Lox-1 Knockdown Inhibits the Effect Of Hng On Reducing Accummentioning
confidence: 99%